Momentum and kinetic energy during the tackle in rugby union - Hendricks, S.; Karpul, D.; Lambert, M. I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The tackle in rugby union is a dynamic and high impact contact situation that occurs frequently during matches and exposes players to a high risk of injury and muscle damage. Large differences in momentum and kinetic energy between the ball-carrier (BC) and tackler (T) have been identified as risk factors for injury and may contribute to the outcome of the tackle. Given the importance of the tackle in rugby union, little is known about the physical components of the tackle in real match situations. Aim The purpose of this study was to firstly quantify momentum and kinetic energy before contact in the tackle during real match situations in 3 competitions (Super 14, Varsity Cup and Under 19 Currie Cup) for the ball-carrier and tackler . Next, the study explored the relationship between these physical components and the outcome of the tackle Methods: Using a two-dimensional scaled version of the field, the velocity of the ball-carrier and tackler were measured 0.5s before contact. Players` weights were obtained from player profiles either from their National Union, Super 14 franchise or Provincial Union. Accordingly, momentum and kinetic was determined. Thereafter, the outcome of the tackle, and tackle location was identified. Results: BC momentum in both types of tackles (front-on 505±209 kg.m/s; side-on 500±186 kg.m/s) was not significantly different to T momentum (front-on 536±217 kg.m/s; side-on 458±183 kg.m/s). Similarly, BC kinetic energy in both types of tackles (front-on 1443±1407 Joules (J); side-on 1741±1262 J) was not significantly different to T momentum (front-on 1422±1009 J; side-on 1294±1043 J). In isolation, the odds of a player succeeding in the tackle is increased by 50% (Odds Ratio (OR) 1.49, 95%Cl 0.51-4.39) when the player enters the contact at a higher P or KE than the opponent. However, considering level of play, type of tackle, player position and distance from set piece, this odds ratio decreased to OR 0.92, 95Cl% 0.25-3.38. Discussion: This is the first study to quantify momentum and kinetic energy before contact in the tackle during real match situations for the ball-carrier and tackler. The lack of differences between level of competition and tackle types may indicate the dynamic nature of the tackle. As expected, the player with the higher momentum or kinetic energy was more likely to succeed in contact. However, when level of competition, type of tackle, player position and distance from set piece were considered, this odds ratio decreased. Using this study as a basis, it is recommended that future studies focus on the relationship between these physical components and the technical characteristics of the ball-carrier and tackler. Also, studying the impact dynamics of the tackle situation and its association with injury is proposed.